Overall and cancer related mortality among patients with ocular inflammation treated with immunosuppressive drugs: retrospective cohort study. (3rd July 2009) - Kempen, John H; Daniel, Ebenezer; Dunn, James P; Foster, C Stephen; Gangaputra, Sapna; Hanish, Asaf; Helzlsouer, Kathy J; Jabs, Douglas A; Kaçmaz, R Oktay; Levy-Clarke, Grace A; Liesegang, Teresa L; Newcomb, Craig W; et al.
Abstract : Context Whether immunosuppressive treatment adversely affects survival is unclear. Objective To assess whether immunosuppressive drugs increase mortality. Design Retrospective cohort study evaluating overall and cancer mortality in relation to immunosuppressive drug exposure among patients with ocular inflammatory diseases. Demographic, clinical, and treatment data derived from medical records, and mortality results from United States National Death Index linkage. The cohort's mortality risk was compared with US vital statistics using standardised mortality ratios. Overall and cancer mortality in relation to use or non-use of immunosuppressive drugs within the cohort was studied with survival analysis. Setting Five tertiary ocular inflammation clinics. Patients 7957 US residents with non-infectious ocular inflammation, 2340 of whom received immunosuppressive drugs during follow up. Exposures Use of antimetabolites, T cell inhibitors, alkylating agents, and tumour necrosis factor inhibitors. Main outcome measures Overall mortality, cancer mortality. Results Over 66 802 person years (17 316 after exposure to immunosuppressive drugs), 936 patients died (1.4/100 person years), 230 (24.6%) from cancer. For patients unexposed to immunosuppressive treatment, risks of death overall (standardised mortality ratio 1.02, 95% confidence interval [CI] 0.94 to 1.11) and from cancer (1.10, 0.93 to 1.29) were similar to those of the US population. Patients who used azathioprine, methotrexate, mycophenolate mofetil, ciclosporin, systemic corticosteroids, or dapsone had overall and cancer mortality similar to that of patients who never took immunosuppressive drugs. In patients who used cyclophosphamide, overall mortality was not increased and cancer mortality was non-significantly increased. Tumour necrosis factor inhibitors were associated with increased overall (adjusted hazard ratio [HR] 1.99, 95% CI 1.00 to 3.98) and cancer mortality (adjusted HR 3.83, 1.13 to 13.01). Conclusions Most commonly used immunosuppressive drugs do not seem to increase overall or cancer mortality. Our results suggesting that tumour necrosis factor inhibitors might increase mortality are less robust than the other findings; additional evidence is needed.